Rationality + consciousness = free will - Hodgson, David (David H.) (New York ; Oxford : Oxford University Press, 2012)
Taking a fresh approach to the question of free will, David Hodgson contends that close consideration of human rationality and human consciousness shows that together they give us free will, in a robust and indeterministic sense, and in a way that is consistent with what science tells us about the world.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Free will and determinism; Responsibility